2016
DOI: 10.18632/oncotarget.6855
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-survivin signaling mediates a poor response to radiotherapy in HER2-positive breast cancers

Abstract: Although radiotherapy resistance is associated with locoregional recurrence and distant metastasis in breast cancers, clinically relevant molecular markers and critical signaling pathways of radioresistant breast cancer are yet to be defined. Herein, we show that HER2-STAT3-survivin regulation is associated with radiotherapy resistance in HER2-positive breast cancers. Depletion of HER2 by siRNA sensitized HER2-positive breast cancer cells to irradiation by decreasing STAT3 activity and survivin, a STAT3 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…HER2 protein overexpression has often been found in clinical breast cancer patients, and the clinical manifestations of such patients are exceptionally poor, including higher degrees of malignancy, strong metastatic ability and clinically low patient survival (9). In addition, it has been reported that radiation resistance often occurs when treating HER2-positive breast cancer patients in clinic (10), which greatly influences radiation therapy. However, at present, few studies have investigated the mechanism involved in the radiosensitivity of HER2-positive breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 protein overexpression has often been found in clinical breast cancer patients, and the clinical manifestations of such patients are exceptionally poor, including higher degrees of malignancy, strong metastatic ability and clinically low patient survival (9). In addition, it has been reported that radiation resistance often occurs when treating HER2-positive breast cancer patients in clinic (10), which greatly influences radiation therapy. However, at present, few studies have investigated the mechanism involved in the radiosensitivity of HER2-positive breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…We also identified Stat3 as the major target of miR-124. It has been shown that STAT3-survivin signaling mediated a poor response to radiotherapy in HER2-positive breast cancers (15). We thus hypothesized that weakly expressed miR-124 might enhance Stat3 expression and activity, contributing to radiotherapy resistance in these cells.…”
mentioning
confidence: 99%
“…One of the most common types of breast cancer is ErBb2/HER2-positive breast cancer, which accounts for 25% -30% of all cases of breast cancer (23). ErbB2 protein is expressed at high levels on the surface of ErBb2-positive breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%